SYNTHETIC CATHINONES AND NEW PSYCHOACTIVE SUBSTANCES IN POLAND: EPIDEMIOLOGY, TOXICOLOGY, AND PUBLIC HEALTH IMPACT - Aleksandra Młocek; Adrianna Truszyńska-Zawisza; Karolina Gorczyca; Natalia Sapeda; Zuzanna Romanowska; Aleksandra Białas; Weronika Lusarczyk; Anna Mandziuk (International Journal of Innovative Technologies in Social Science, 2025)
Introduction and purpose: The rapid emergence and increasing prevalence of synthetic cathinones, a prominent subgroup of new psychoactive substances (NPSs), pose a significant and evolving public health challenge in Poland. These substances, often marketed as “bath salts” or “legal highs,” are chemically related to cathinone, a natural stimulant found in the khat plant, but are synthetically modified to evade existing drug control regulations while producing potent stimulant effects [1] Over recent years, Poland has become a major hub for the production, distribution, and consumption of synthetic cathinones, with large quantities seized annually and numerous clandestine laboratories dismantled [3]. This dynamic and complex illicit market, combined with the chemical diversity and unpredictable toxicity of synthetic cathinones, complicates clinical diagnosis, treatment, and forensic toxicological analysis [2] This study aims to provide a comprehensive overview of the epidemiological trends, toxicological profiles, clinical manifestations, and public health implications of synthetic cathinone intoxications in Poland. Materials and Methods: Data for this study were primarily obtained from national poison registries, including the SYSTEM FOR MONITORING INFORMATION ON SUBSTITUTE AGENTS AND NEW PSYCHOACTIVE SUBSTANCES (SMIOD), and official reports submitted to the Chief Sanitary Inspectorate (GIS) during 2024 [3]. The dataset encompassed detailed information on demographics, geographic distribution of cases, specific substances involved, observed clinical presentations, and patient outcomes related to intoxication events. Clinical observations were further complemented by robust toxicological analyses of biological samples (blood, urine). Conclusions: This study unequivocally underscores that synthetic cathinones represent a growing and increasingly complex challenge to public health in Poland, contributing significantly to rising morbidity and mortality rates associated with substance intoxications [2] .The findings highlight the critical need for continuous epidemiological surveillance, enhanced public awareness campaigns (especially tailored to identified seasonal peaks), and improved rapid diagnostic capabilities within clinical settings settings [4]. Effective management of this public health crisis necessitates a deeply integrated, multidisciplinary approach that combines advanced toxicological analysis, clinical expertise, and coordinated public health interventions. Addressing this pervasive issue proactively and adapting to the dynamic nature of the NPS market will be essential to mitigate the profound adverse health and social consequences associated with the widespread use of synthetic cathinones.